SEISMIC ANALYSIS OF A SHEAR BUILDING MODEL - Chtcot, Ronnie; Brasil, Reyolando M. L. R. F. (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Although strong seismic events are rare in Brazil, Brazilian structural engineers are frequently involved in such analysis for neighboring Latin American countries. Here, weÂ present a study on the linear seismic response of a shear building mathematical model of aÂ tall building. Step-by-step numerical time integration via Finite Differences is implemented toÂ solve the ordinary differential equations of motion. Seismic base excitation, of random nature, is not, in general, available. Usual National Building Codes for seismic resistant constructions don’t provide design base accelerograms to compute the inertia forces at eachÂ pavement of the building. The standard information is the so called elastic design spectrum,Â that provides the maximum response acceleration for a one degree of freedom linear dampedÂ system for each country. Much research is being developed in order to generate artificial base motion accelerograms compatible with these Code spectra. We presented a proposal forÂ generating artificial base motion accelerograms compatible with the Brazilian National CodeÂ for Seismic Resistant Building. A base motion accelerogram generate according to ourÂ proposal was applied to a 10-store shear building model. Keywords: structural dynamics, seismic analysis, Brazilian seismic resistant building code.